Integrated athlete acceleration program (paket) potential sports of koni depok - Lutfia Dzulfani; Gustiana Mega Anggita (Gladi : Jurnal Ilmu Keolahragaan, 2022)
This study aims to determine the achievement development program carried out by KONI Depok covering human resources for athletes and coaches, implementation of coaching programs, facilities and infrastructure as well as management organization in the Integrated Athlete Acceleration Program (PAKET) using qualitative descriptive methods. Data collection methods used are observation, interviews, and documentation. The research targets consisted of 5 athletes, 5 coaches, and 5 sports administrators from 5 sports that run. Check the validity of the data by triangulation of sources and methods. Data analysis techniques used are data collection, data reduction, data presentation, and drawing conclusions. The results of the study: 1) The potential of human resources including athletes and coaches is good and has the opportunity to get medals at the Provincial Sports Week (PORPROV), recruitment of athletes using a track record of achievement and coaches with coaching certification. 2) The implementation of coaching can be said to be good, the coaching stage is carried out to foster athletes and provide an ideal training program. 3) The facilities provided are adequate, but the infrastructure is still not up to standard. 4) The management organization can be said to be running well according to the duties and obligations.